THE NOT SO PASSÉ MBA: PODCASTS AS MARKETING CASES. Issue 2 (3rd April 2019) - VanMeter, Rebecca A.; Schetzsle, Stacey; Howie, Katharine
Abstract : Traditional MBA programs and course delivery methods have come under increased scrutiny, to the point of being labeled passé. Specific criticisms include the relevance of the material and an inability to prepare students for the real world. This paper presents a teaching innovation whereby the textbook chapters align with short podcasts that serve as example cases, replacing traditional case studies with recent podcasts and applying marketing concepts to the current business situation addressed by the individual podcast. A description of key techniques, data, and examples for course implementation is presented.